Estrategias educativas para el desarrollo socio-afectivo en los estudiantes de séptimo año de la unidad educativa particular “La Salle”. - Mena Barthelotty, Alicia de las Mercedes (2020)
The present research on the socio-affective development of students has led to an understanding of the performance of children in their homes and in their institution; therefore, it has been necessary to increase this problem, which will help to improve the work between teachers and students, parents and children about a better coexistence and change of attitude in each of the stakeholders. Its fundamental objective is to analyze the effect produced by the application of a proposal of educational strategies for the socio-affective development of the Seventh year students in the Private Educational Unit La Salle; using the mixed methodology since it allowed for the analysis of qualities and behaviors, which will later be interpreted critically identifying the potentialities of change and social action. And finally, as a more relevant result, after various work meetings, the socio-affective problems of the students became evident; therefore, in discovering these and other elements, the aim is to put forward new educational strategies to resolve the aforementioned problems.